Farmers’ Awareness and Use of Automated Teller Machines (ATMs) in Selected Communities in Enugu North Senatorial Zone, Enugu State - C L Onovo; I A Enwelu (Journal of Agricultural Extension, 2014)
The study determined farmers’ awareness and use of automated teller machines (ATMs) in some selected communities in Enugu North Senatorial Zone of Enugu State. Interview schedule was used to collect data from a sample size of sixty (60) respondents using purposive selection. Percentage, frequency, and mean scores were used in analyzing data. Majority of the respondents were aware of bank account (95.02%), withdrawal booklet (91.7%) and ATM card (81.7) while few were aware of ATM function keys (41.7%) and ATM cash dispenser (20.0%). The main sources of information on ATMs were bank personnel (80.0%), friends and neighbours (75.0%), family members (73.3%). Other sources were newspaper (43.3%), schools (36.7%) and extension workers (18.3%). A greater percentage of farmers (55%) indicated the use of ATM for cash withdrawals while other transactions included transfer of funds (16.7%) and paying bills/fees/taxes (15.0%). The serious constraints to the use of ATM included fraud (M=1.65), charges on the use of ATM (M=1.22) and network problems (M=1.22). Perceived benefits of the use of ATM included time saving (M=2.85), cash withdrawal (M=2.70), easy access (M=2.60) and greater efficiency (M=2.45). The study recommends that public awareness should be created through workshops, seminars and conferences as well as mounting multiple security cameras and security guards to reduce fraud.